Pesque-solte: pesca repetitiva, variáveis hematológicas e parasitismo no peixe híbrido tambacu - Varandas, Daniela Nomura; Martins, Maurício Laterça; Moraes, Flávio Ruas De [UNESP]; Ramos, Fabrício Menezes; Santos, Rudã Fernandes Brandão [UNESP]; Fujimoto, Rodrigo Yudi (Empresa Brasileira de Pesquisa Agropecuária (EMBRAPA), 2013)
The objective of this work was to evaluate the hematological and parasitological responses of tambacu (Colossoma macropomum x Piaractus mesopotamicus) subjected to catch-and-release stress and to different stocking densities in a catch-and-release system. Two hundred and ten fish with mean initial weight of 785.33±152.02 g and mean total length of 34.43±2.21 cm were maintained in ponds and divided into three groups: without fishing and low density (G1), with fishing and low density (G2), and with fishing and high density (G3). No significant differences were observed between the mean values for hemoglobin concentration, erythrocyte number, differential counting of leukocytes, and glucose. The fish from the G3 group showed higher parasite and thrombocyte numbers, and lower weight gain and hematocrit. The activity of catch-and-release, associated with high stocking density, can disrupt organic balance and animal performance, favoring parasitosis.

O objetivo deste trabalho foi avaliar a resposta hematológica e parasitológica de tambacus (Colossoma macropomum x Piaractus mesopotamicus) submetidos ao estresse de captura e a diferentes densidades de estocagem, em sistema de pesque-solte. Foram utilizados 210 peixes com peso médio inicial de 785,33±152,02 g e comprimento total médio de 34,43±2,21 cm, mantidos em viveiros escavados e divididos em três grupos: sem pesca e baixa densidade (G1), com pesca e baixa densidade (G2), e com pesca e alta densidade (G3). Não houve diferença significativa entre os valores médios da concentração de hemoglobina, do número de eritrócitos, da contagem diferencial de leucócitos e da glicose. Os peixes do grupo G3 apresentaram número maior de parasitos e trombócitos, e menor ganho de peso e hematócrito. A atividade de pesque-solte, aliada à alta densidade de estocagem, pode prejudicar o equilíbrio orgânico e o desempenho zootécnico, o que favorece a parasitose.
Catch-and-release: repetitive fishing, hematological variables and parasitism in the tambacu hybrid fish
Keywords: Colossoma macropomum; Piaractus mesopotamicus; stocking density; Parasites; Sports fishing; Colossoma macropomum; Piaractus mesopotamicus; densidade de cultivo; Parasito; pesca esportiva